Analysis of the Implementation of Restorative Justice in Handling the Crime of Theft of Children at the Cirebon City Police - Melyssa, Dona; Fadiyah, Hamda; Fazria, Vitra Nur; Waluyadi, Waluyadi; Nurhaqi, Ari (Journal Of Social Science (JoSS), 2025)
The rise in juvenile theft cases in Cirebon, Indonesia, underscores the need for restorative justice (RJ) as an alternative to punitive measures, aligning with child protection laws (SPPA Law No. 11/2012) and Perkapolri No. 8/2021. However, RJ’s implementation faces challenges, including social stigma and inconsistent adherence to rehabilitation principles. This study analyzes RJ’s effectiveness in handling juvenile theft at the Cirebon City Police, examining its compliance with legal frameworks and on-ground practicality. A normative-empirical approach was employed, combining analysis of national laws with primary data from police interviews and case observations. RJ implementation was effective in fostering victim-perpetrator reconciliation and reducing recidivism, contingent on voluntary agreements and mediator competence. Key barriers included limited public awareness, rigid legal thresholds for diversion, and resource gaps in facilitator training. The study advocates for policy reforms to expand RJ’s applicability beyond minor offenses, enhanced training for law enforcement, and community education to mitigate stigma. It contributes to localized RJ models in Indonesia’s juvenile justice system.